Significance of data integration and ETL in business intelligence framework for higher education - Mohamad Rodzi, Nur Alia Hamizah (2015)
One of the important component toward developing a business intelligence framework is data integration. It is used to combine data from different academic data sources and integrate it together before stored it in integrated manner as needed by higher education institute. ETL is the common steps to integrate data and transform it to compatible in targeted destination system. This paper use Universiti Teknologi Malaysia (UTM) as the case study for further understanding on the relation of data integration with extract, transform and load (ETL) process. Data integration plays its important role in BI framework as it integrates different attributes from different tables during transformation process in ETL. ETL process performs data cleaning during extraction process and load significant data into data warehouse. Thus, it maintains the integrity of data to be used for decision making and reporting. This paper will highlight the importance of data integration and ETL in business intelligence framework and its significance for better higher education management.